(untitled) (Comprehensive Journal of Science, 2026)
The ability of social institutions to meet clients’ needs and desires and to provide them in the best possible manner and according to the required specifications, within defined standards, can only be achieved through attaining a high level of service quality in these institutions. Such quality is what ensures excellence and distinction among state institutions. Accordingly, service quality has become a fundamental requirement and a prerequisite for institutional performance. Therefore, it is necessary to overcome the obstacles that hinder the achievement of this quality. From this perspective, the importance of the present study emerges, as it seeks to identify and examine the relationship between the existence of obstacles and the quality of services provided in social institutions.